1983
DOI: 10.1079/bjn19830116
|View full text |Cite
|
Sign up to set email alerts
|

The nutritive value of rumen micro-organisms in ruminants

Abstract: 1. An experiment was conducted with three sheep maintained entirely by intragastric nutrition to estimate the digestibility of isolated individual constituents and amino acids (AA) of rumen micro-organisms (RMO) in the small intestine.2. Five levels of RMO were infused into the abomasum. The apparent and true disappearance of the individual components were measured by regression of abomasal input on the passage at the ileum. In order to proceed further to state the AA requirement of ruminants precisely it is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(18 citation statements)
references
References 14 publications
1
16
0
1
Order By: Relevance
“…The proportions of [ 14 C]methionine and [ 35 S]amino acids representing cysteine and methionine appearing unabsorbed at the terminal ileum averaged 013 and 002. The value for cysteine plus methionine labelled with 35 S appears rather high compared with those of cysteine reported for rumen bacteria by Elliot & Little (1977) and Storm et al (1983) but they are similar to values reported by Armstrong & Hutton (1975). If the absorption of lysine, tyrosine, cysteine and methionine are considered to be representative of the digestibility of other amino acids in fungal proteins, the results in Table 1 show that the true digestibility of fungal proteins is c. 0-9.…”
Section: R E S U L T S a N D Discussionsupporting
confidence: 88%
“…The proportions of [ 14 C]methionine and [ 35 S]amino acids representing cysteine and methionine appearing unabsorbed at the terminal ileum averaged 013 and 002. The value for cysteine plus methionine labelled with 35 S appears rather high compared with those of cysteine reported for rumen bacteria by Elliot & Little (1977) and Storm et al (1983) but they are similar to values reported by Armstrong & Hutton (1975). If the absorption of lysine, tyrosine, cysteine and methionine are considered to be representative of the digestibility of other amino acids in fungal proteins, the results in Table 1 show that the true digestibility of fungal proteins is c. 0-9.…”
Section: R E S U L T S a N D Discussionsupporting
confidence: 88%
“…If so, rumen microbial NAN flow at the ileum is likely to be slightly overestimated and consequently true digestibility and absorption in the small intestine slightly underestimated. The digestibility of rumen microbial NAN in the small intestine did not differ between diets and the overall mean value was 0.72 whilst, in other studies, values of 0.71 for 35S-labelled bacteria in the intestines of sheep (Bird, 1972), 0.75 and 0-85 for I5N-and 36S-labelled bacteria respectively in young cattle (Salter & Smith, 1978) and 0-82 in sheep (Storm et al 1983) have been obtained.…”
Section: N Digestion In the Small Intestinementioning
confidence: 63%
“…Proteins that escape microbial degradation in the rumen are particularly important for growth, development, gluconeogenesis, and possibly toxin excretion when the amino acid profiles of the escape proteins differ from microbial proteins (Maiga et al 1996). Both CSM and DDG provide a source of amino acids to the small intestine that differ from the amino acids available from microbial protein (Storm and Orskov 1983;O'Mara et al 1997; Table 5). CSM provides more arginine and glutamine to the small intestine, while DDG provides more glutamine and proline to the small intestine.…”
Section: Discussionmentioning
confidence: 99%